Characteristics of Iranian Covid-19 Clinical Trials - Meisam Dastani; Farshid Danesh; Mohammad Ghorbani (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: The widespread prevalence of COVID-19 has led to an unprecedented effort to find effective treatments which have increased clinical trial studies. Therefore, this study aimed to determine the characteristics of Iranian Covid-19 clinical trial studies. Methods: This is a cross-sectional descriptive study. The data relating to Iranian Covid-19 clinical trials were extracted from the Iranian Registry of Clinical Trials (IRCT) in February 2020 and transferred to an Excell Microsoft Office software. The descriptive statistical data were presented as frequency and percentages to describe the key characteristics of the extracted clinical trials.   Results: At the time of data collection, 491 clinical trials associated with COVID-19 have been recorded in IRCT, 91.65% of which were supported by governmental organizations. An examination of the data indicated that the method of allocation in 83.09% and 86.67% of clinical trials has been randomized assignment and parallel assignment, respectively. In addition, the placebo has been used in 69.65% of clinical trials. It is worth mentioning that blinding was not carried out in 50.1% of these studies. Based on the findings, 81.67% of the clinical trials have been conducted for the purpose of treatment, and drug treatment accounted for 70.47% of the intervention employed in these clinical trials. Conclusion: The results of this study provided a summary of the status and characteristics of COVID-19 clinical trials recorded in IRCT. Regarding the fact that the majority of these studies are supported by governmental organizations, it is recommended that financial resources of private pharmaceutical companies should be used under the supervision and approval of the Food and Drug Administration as a support for these clinical trials.